2014
DOI: 10.1111/hpb.12176
|View full text |Cite
|
Sign up to set email alerts
|

Altered lysophosphatidic acid (LPA) receptor expression during hepatic regeneration in a mouse model of partial hepatectomy

Abstract: Liver regeneration following PHx is associated with significant changes in circulating LPA and hepatic LPAR1, LPAR3 and LPAR6 expression in a time- and cell-dependent manner. Furthermore, changes in LPA-LPAR post-PHx occur after the first round of hepatocyte division is complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Moreover, LPAR6 was more widely stained than LPAR1 and LPAR3. These results suggest that LPA receptors (LPAR1, LPAR3, LPAR6) can promote liver regeneration after hepatectomy [128].…”
Section: Lpar and Liver Regenerationmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, LPAR6 was more widely stained than LPAR1 and LPAR3. These results suggest that LPA receptors (LPAR1, LPAR3, LPAR6) can promote liver regeneration after hepatectomy [128].…”
Section: Lpar and Liver Regenerationmentioning
confidence: 72%
“…Furthermore, blocking the production of inflammatory cytokines (TNF-α and IL-1β) protects against APAP-induced acute liver injury. But this process was independent of LPA receptors [128]. Hepatitis was a key factor in the development of liver fibrosis.…”
Section: Lpar and Liver Fibrosismentioning
confidence: 99%
“…Indeed, the relative absence of well-characterized LPAR subtypes (LPARs1–5) within the liver presents somewhat of a paradox in understanding how LPA affects liver function and hepatic pathogenesis. For example, in animal models, correlations between circulating LPA and degree of underlying liver injury are reported [ 41 ] yet LPARs 1–5 are barely detectable (if at all) in rodent hepatocytes/liver tissue [ 28 ]. Similarly, cirrhotic and HCC patients exhibit elevated serum LPA levels, while the relative expression of LPA species in patients at risk for developing HCC suggest serum LPA profiles may be beneficial in identifying those patients with HCC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by our group and others now report LPAR6, the most recently characterized LPAR subtype [ 24 , 25 ], is expressed in normal liver/hepatocytes, and is significantly elevated in human HCC [ 26 , 27 ] and regenerating rodent liver [ 28 ]. During the course of these studies we reported LPAR1 and LPAR3 expression was increased in a subset of human HCC and cirrhotic non-tumor liver (NTL) compared to liver from non-tumor burdened patients [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ikeda et al first demonstrated that LPA might affect the proliferation of hepatocytes and stellate cells in those liver diseases that disrupted platelet activation [ 8 ]. Recently, by using a partial hepatectomy mouse model, Simo et al found that liver regeneration after partial hepatectomy was associated with significant changes in circulating LPA levels (LPA increased significantly at 72 hours post- partial hepatectomy to 6.30 ± 0.67 μM as compared to 3.58 ± 0.37 μM in sham-operated mice) and that hepatic mRNA levels of LPAR1, LPAR3, and LPAR6 were expressed in a time- and cell-dependent manner [ 9 ]. Additionally, their immunohistochemical staining results revealed that LPAR1 protein was expressed in non-parenchyma cells, and that LPAR3 and LPAR6 proteins were widely distributed in regenerating liver tissue [ 9 ].…”
Section: Introductionmentioning
confidence: 99%